Humanization in medical education in Brazil (Research, Society and Development, 2022)
Introduction: the training of medical professionals has been undergoing changes, among which humanization is highlighted. Objective: to understand how humanization in medical education has been addressed in the Brazilian scientific literature, seeking to analyze the characteristics of published studies, discovering the concepts attributed to the term humanization and identifying pedagogical strategies that favor the development of humanization. Methodology: exploratory-descriptive study, consisting of an integrative literature review. The search for studies took place in 2018, in the Virtual Health Library, using intersections of descriptors: education, medical education, medical students, humanization and humanization of care. After the crossings, the articles were saved in folders, named from 01 to 145. The titles and abstracts were read, applying inclusion and exclusion criteria, leaving 53 articles for full reading, of which 42 studies were selected as they were suitable. to the research objectives. Results: from the analyzed studies, 27 presented a concept of humanization related to listening, empathy, bonding, ambience and communication, showing a relationship with the concept assumed by the National Humanization Policy. Another 15 studies related humanization with integrality, referring to different knowledge, teamwork, culture, social and emotional vision. Also, 22 studies mentioned humanization as a guarantee of rights, covering ethics and social responsibility. Conclusion: it is concluded that humanization is a term treated in a polysemic way in the scientific literature and that different pedagogical strategies have been used with the purpose of promoting humanization in Brazilian medical education.